A tangle of spells - Harrison, Michelle (Simon & Schuster UK Ltd, 2021)
Escape into a brand-new Pinch of Magic Adventure from bestselling Michelle Harrison, where everyone knows that magic and trouble go hand in hand . . . It should have been a fresh start for the Widdershins sisters, Betty, Fliss and Charlie, who have left the misty gloom of Crowstone for a new life in the pretty village of Pendlewick. But all is not as it seems and as one of their own begins to slip away from them, the sisters find themselves in a race against time to break a dark magic that has cast a spell over the village. Step into the bestselling Pinch of Magic Adventures in this spellbinding story from Michelle Harrison, winner of the Waterstones Children's Book Prize. Discover more from the Widdershins sisters in A Pinch of Magic and A Sprinkle of Sorcery.